ELECTROCARDIOGRAPHIC DYNAMICS OF THE ST SEGMENT AND T WAVE IN NON–ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION - Khalilov, Sh.J. (World of Medicine and Biology, 2025)
To assess the characteristics and dynamics of ST-segment and T-wave changes in non–ST-segment elevation myocardial infarction, 200 patients were examined, including 164 men and 36 women; the mean age was 62.21±9.38 years. Based on coronary angiography findings, patients were divided into two groups: Group I included 94 patients with non–ST-segment elevation myocardial infarction and non-obstructive coronary artery lesions (stenosis
Keywords: non-ST-segment elevation myocardial infarction; electrocardiogram; ischemic heart disease; obstructive and non-obstructive coronary artery lesions